ANALISIS PRODUKTIVITAS DAN PENDAPATAN USAHATANI SAYURAN DAUN DALAM MASA PANDEMI - Agas, Angelina Hartini; Adar, Damianus; Levis, Leta R. (Buletin Ilmiah Impas, 2024)
The COVID-19 pandemic has an impact on various sectors, one of which is agriculture. The decrease in domestic agricultural production due to the COVID-19 pandemic threatens the fulfilment of people's food needs. This study aims to determine the productivity, income, and factors affecting leaf vegetable farming before and during the Covid-19 pandemic. This research was conducted in Noelbaki Village, with 50 respondents. The research method used a survey method. The results showed that the productivity and income of mustard, kale, and spinach leaf vegetable farms decreased due to the scarcity of production facilities. This is evidenced by the results of the mean difference test showing that there are significant differences in the productivity and income of vegetable farms before and during the Covid-19 pandemic. Factors that significantly affect the productivity of mustard vegetable farms are fertilizer and the Covid-19 pandemic, for kale vegetables are seeds, fertilizer, and the Covid-19 pandemic and for spinach vegetable farms are the Covid-19 pandemic.